Enhancing Enterprise Performance: The Benefits and Rising Demand of Deploying SAP HANA on Linux VMs in Azure - Ratnangi Nirek (North American Journal of Engineering Research, 2021)
The benefits and growing acceptance of running SAP HANA on Linux virtual machines (VMs) on Microsoft Azure are examined in this article. Due to its high-performance, in-memory database capabilities, SAP HANA is now a vital part of any business looking to improve its analytics and data processing skills. Businesses may optimize their operations and gain a competitive edge with the cost-effective, scalable, and secure solution provided by SAP HANA deployed on Linux virtual machines in Azure. The technological advantages, application scenarios, and potential adoption trends of this architecture are covered in this article.